Rooftop terraces as an experiential tourist offer: the case of Madrid (Spain) - Babinger, Frank; Serrano-Cambronero, María Milagros (Revista de Estudios Andaluces, 2021)
This article focuses on the analysis of rooftop terraces in the city of Madrid (Spain) as an example of the new tourist demands in urban environments. In this way, they stand out as an example of an offer aimed to satisfy the needs of post-modern tourists who demand quality tourist experiences. The methodology was based firstly on a bibliographic review, secondly on the search for terraces through specialized web pages, fieldwork and their subsequent georeferencing, and finally in the analysis of the information. The spatial distribution of the terraces is presented, through updated cartography, carried out after the georeferencing of the terraces. It is worth noting that the rooftop terraces are directly linked to the offer of experiential and quality tourism demanded by tourists, while their geographical distribution shows their clear relationship with the most touristic area of the city of Madrid.